Modality-specific peripheral antinociceptive effects of μ-opioid agonists on heat and mechanical stimuli: Contribution of sigma-1 receptors. (June 2018) - Montilla-García, Ángeles; Perazzoli, Gloria; Tejada, Miguel Á.; González-Cano, Rafael; Sánchez-Fernández, Cristina; Cobos, Enrique J.; Baeyens, José M.
Abstract: Morphine induces peripherally μ-opioid-mediated antinociception to heat but not to mechanical stimulation. Peripheral sigma-1 receptors tonically inhibit μ-opioid antinociception to mechanical stimuli, but it is unknown whether they modulate μ-opioid heat antinociception. We hypothesized that sigma-1 receptors might play a role in the modality-specific peripheral antinociceptive effects of morphine and other clinically relevant μ-opioid agonists. Mechanical nociception was assessed in mice with the paw pressure test (450 g), and heat nociception with the unilateral hot plate (55 °C) test. Local peripheral (intraplantar) administration of morphine, buprenorphine or oxycodone did not induce antinociception to mechanical stimulation but had dose-dependent antinociceptive effects on heat stimuli. Local sigma-1 antagonism unmasked peripheral antinociception by μ-opioid agonists to mechanical stimuli, but did not modify their effects on heat stimulation. TRPV1+ and IB4+ cells are segregated populations of small neurons in the dorsal root ganglia (DRG) and the density of sigma-1 receptors was higher in IB4+ cells than in the rest of small nociceptive neurons. The in vivo ablation of TRPV1-expressing neurons with resiniferatoxin did not alter IB4+ neurons in the DRG, mechanical nociception, or the effects of sigma-1 antagonism on local morphine antinociception in this type of stimulus. However, it impaired the responses to heat stimuli and the effect of local morphine on heat nociception. In conclusion, peripheral opioid antinociception to mechanical stimuli is limited by sigma-1 tonic inhibitory actions, whereas peripheral opioid antinociception to heat stimuli (produced in TRPV1-expressing neurons) is not. Therefore, sigma-1 receptors contribute to the modality-specific peripheral effects of opioid analgesics. Highlights: μ-opioid agonists induce peripheral antinociception to heat stimulus. μ-opioid agonists do not induce peripheral antinociception to mechanical stimulus. σ1 receptors do not modulate peripheral μ-opioid antinociception to heat stimulus. σ1 receptors limit peripheral μ-opioid antinociception to mechanical stimulus. σ1 receptors contribute to the modality-specific peripheral effects of opioids.